The Role of Job Satisfaction in Mediating the Influence of Human Relations, Work Ethic, and Organizational Culture on Employee Performance at PT. XYZ - Edo Andrefson; Ramadhi Ramadhi (CV. Ulil Albab Corp, 2025)
This study aims to analyze the effects of human relations, work ethic, and organizational culture on job satisfaction and employee performance at PT. XYZ. The research uses a quantitative approach with an explanatory design. The population consists of 98 employees, and the entire population is used as the sample due to the small size, employing a saturated sampling technique. Data analysis is conducted using SmartPLS 4.0 (Partial Least Squares) to examine structural models and relationships between the variables. The results show that human relations, work ethic, and organizational culture significantly affect job satisfaction. Job satisfaction, in turn, has a significant impact on employee performance and can mediate the effect of human relations and organizational culture on performance. However, work ethic does not significantly affect employee performance, and human relations do not mediate this relationship. The findings suggest that improving human relations, work ethic, and organizational culture can enhance job satisfaction, which in turn boosts employee performance. This study provides valuable insights for policy development at PT. XYZ to improve employee engagement and productivity